Calificación de salas limpias del área de pesada de productos galénicos en un laboratorio farmacéutico nacional - Bazán Aliaga, Julia Stefanny (2023)
The main objective this report is to explain the actions carried out in the process of qualifyin clean rooms within laboratory of the national production galenic products. This process is important because is a critical point within the Good Manufacturing Practices Manual (GMP), the same one that serves as a guide during inspections for Certification, Recertification and Inopinate Inspections, it is considered as a critical Non-conformity. The tests carried out during the qualification of the weighing room are Temperature and Humidity, which has as Technical Specification ≤ 30 °C and Humidity ≤ 80 %, results were obtained that were within the specification in each of the rooms that make up the weighing area. For the Light Intensity test, the specifications are: ≥ 500 Lux, for each of the points, obtaining 537 lux as the lowest average result and 583 lux as the highest result. Being within specification. In the differential pressure and air renewal per hour, results were also obtained within the specification, the same ones that are expressed in the annexes of this report. The Particle Count test, for suspended particles with a size between 0.5µm and 5µm, gave a satisfactory result, according to the area in m2 of the weighing room. According to the results obtained in the tests carried out, all within specification, it is necessary to indicate that our weighing room of the national pharmaceutical laboratory for the production of galenics, is suitable to perform the functions and tasks that are typical of the fractionation and dispensing of raw materials for the manufacture of galenics for internal and external use